Keterpaparan Program GenRe (Generasi Berencana) dan Perilaku Pacaran Remaja Jawa Timur, Indonesia - Siswantara, Pulung; Rachmayanti, Riris Diana; Muthmainnah, Muthmainnah; Bayumi, Febrianti Qisti Arrum; Religia, Wandera Ahmad (Jurnal Promosi Kesehatan Indonesia, 2022)
Background: According to Population and Family Planning Agency (BKKBN), adolescents are aged 10-24 years and are not married. Indonesian Basic Health Research (RISKESDAS) 2018 showed around 58.8% of adolescents aged 10-19 years had been married and had had a pregnancy. The Indonesian Demographic and Health Survey (SDKI) results revealed that risk behavior among male junior and senior high school students was around 8.06%, and female were 4.17%. This study aimed to determine the correlation between the Planning Generation (GenRe) Program knowledge and adolescents’ characteristics with dating experience in East Java Province. Method: This research was a cross-sectional study. Secondary data were collected from the 2019 Program Performance and Accountability Survey (SKAP) and were analyzed descriptively with cross-tabulation and chi-square tests. The risk estimate calculation was also carried out to identify the Odd Ratio (OR). The sample used was 5,300 adolescents in East Java Province after weighting. The research variables consisted of dating behavior in adolescents, age, gender, and adolescents' knowledge about GenRe, HIV/AIDS, drugs, and Sexually Transmitted Infections (STIs) and Adolescent Reproductive Health Program.Results: The results showed that 41.80% of adolescents in East Java had dated. There was a significant correlation between dating behavior with adolescents’ knowledge about GenRe, HIV/AIDS, drugs, and Sexually Transmitted Infections (STIs) and Adolescent Reproductive Health Program (P-Value = 0.00). Dating behavior also had a significant correlation with age (P-Value = 0.00) and gender (P-Value = 0.00). This study concluded that there was a correlation between dating behavior in adolescents in East Java Province with age, gender, and adolescents’ knowledge about GenRe, HIV/AIDS, drugs, Sexually Transmitted Infection (STIs), and Adolescent Reproductive Health Program. They were strengthening the GenRe program through the introduction, explanation of program activities, and the process of youth involvement. So far, teenagers only know the name of the GenRe program. This action needs to be applied to prevent negative effects caused by dating behavior, such as premarital sex, unwanted pregnancy, and early marriage.